2015
DOI: 10.1055/s-0035-1570313
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Gait in Elderly Group

Abstract: Introduction  The process of aging could lead to seniors being more prone to falls, which affects their quality of life.Objective  The objective of this study is to investigate the relationship between quality of life and gait in the elderly.Methods  We used World Health Organization Quality of Life-Brief (WHOQOL-Brief) Brazilian version and the Dynamic Gait Index to assess fifty-six volunteers from the northeast of Brazil. Ages ranged from 60 to 85 years.Results  The Dynamic Gait Index, which indicates the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…In particular, because the prevalence of glaucoma is associated with advancing age, quality of life with glaucoma is a primary issue in the elderly [5] . Various quality of life factors such as physical condition (postural control, muscle power, and gait) and psychological condition (emotional security and depression) are affected by glaucoma [8–11] . Among those factors, gait function is perhaps the most important factor affecting independent daily activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, because the prevalence of glaucoma is associated with advancing age, quality of life with glaucoma is a primary issue in the elderly [5] . Various quality of life factors such as physical condition (postural control, muscle power, and gait) and psychological condition (emotional security and depression) are affected by glaucoma [8–11] . Among those factors, gait function is perhaps the most important factor affecting independent daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Various quality of life factors such as physical condition (postural control, muscle power, and gait) and psychological condition (emotional security and depression) are affected by glaucoma. [8][9][10][11] Among those factors, gait function is perhaps the most important factor affecting independent daily activities. Many studies have reported on gait function following glaucoma.…”
Section: Introductionmentioning
confidence: 99%